Application of the Principal Component Analysis to explore the relation between land use and solid waste generation in the Duy Tien district, Ha Nam Province, Vietnam - Cu, Pham Van; Charrette, Philippe; Dieu, Dinh Thi; Hai, Pham Ngoc; Toan, Le Quang (VNU Journal of Science: Earth and Environmental Sciences, 2009)
Abstract